دراسة تطبيقية لبعض الآيات القرآنية التي وقع فيها الإشكال (An Applied Study on Chosen Problematic Quranic Verses) - بنت حسن بن محمد تركي نبيلة (Journal of Islam in Asia (E-ISSN 2289-8077), 2021)
تهدف هذه الدراسة إلى بيان مفهوم مشكل القرآن، وذكر علة وجوده، ودراسة تطبيقية لمشكل القرآن الكريم. وقد اتبعت في هذه الدراسة أسلوب المنهج الاستقرائي الوصفي، حيث قمت بتتبع الدلالات اللغوية لمفردة مشكل وتعريف العلماء له اصطلاحًا وخلصت إلى وصف مفهوم المشكل، وبينت حكمة وجود المشكل في القرآن الكريم، ثم الدَّراسة التطّبيقية لآيات وقع الإشكال فيها عند البعض، وقفت من خلالها على توجيه هذا الإشكال الواقع في الآية، وتعرضت لأقوال العلماء في دفع هذا الإشكال وأجوبة المفسّرين المحققين حول ذلك، ثم الترجيح بين تلك الأقوال ما أمكن. وقد خلصت إلى النتيجة التالية: وهي أنه بد لمن أراد التمرس في دفع المشكل في ذلك من الرجوع إلى أقوال العلماء المحققين ومعرفة كيفية طرائقهم في دفع الإشكال، علما بأن بعض الإشكالات التي تقع قد يعرضها المفسر لطارئ يطرأ في الذهن، فالإشكال فيها نسبي قد يشكل على أحد ما لا يشكل على الآخر؛ فتعرض لمفسر دون آخر، وتعرض لأفراد دون آخرين، هذا مع ما ظهر من عناية المفسرين في توجيههم لتلك الإشكالات التي تقع ودحضهم لكل الشبه بالأدلة والبراهين. الكلمات المفتاحية: دراسة، تطبيقية، مشكل، الإشكال، آيات. Abstract This study aims to clarify the concept of Mushkil al-Qurān, the wisdom behind it, and to present an applied study on Mushkil al-Qurān. The inductive descriptive method was followed by looking closely at the linguistic semantics of the word mushkil and its terminological definition presented by the scholars. A description of the concept of al-mushkil was concluded, as well as the wisdom behind having al-mushkil in Quran. Then, the applied study on certain problematic verses was conducted by raising the ambiguity (al-Ishkāl) related to them with referring to the opinions of the scholars and mufasirīn on how to remove the ambiguity, and finally suggesting tarjīh (lit. outweighing) between those opinions. The study concluded that whoever wishes to be experienced and skillful in dealing with Mushkil al-Qurān must refer to the opinions and ways of scholars in dealing with those problematic verses, while keeping in mind that the reality that certain verses are problematic is relative as some mufasirīn might consider it as such while others might not. Mufasirūn have been meticulous in dealing with the problematic verses and have been refuting the misconceptions with sound proofs and arguments. Keywords: Applied, Study, Mushkil, Al-Ishkāl, Verses.